COVID-19-Related Mental Health Burdens: Impact of Educational Level and Relationship Status Among Low-Income Earners of Western Uganda - Lemuel, Ann Monima; Usman, Ibe Michael; Kasozi, Keneth Iceland; Alghamdi, Saad; Aigbogun, Eric Osamudiamwen; Archibong, Victor; Ssebuufu, Robinson; Kabanyoro, Annet; Ifie, Josiah Eseoghene; Swase, Dominic Terkimbi; Ssempijja, Fred; Ayuba, John Tabakwot; et al. (Frontiers in Public Health, 2021)
Objective: The study aimed to investigate the relationship between mental health with the level of education, relationship status and awareness on mental health among low-income earners in Western Uganda. Methods: This was a cross-sectional descriptive study carried out amongst 253 participants. Anxiety, anger, and depression were assessed using a modified generalized anxiety disorder (GAD-7), Spielberger’s State-Trait Anger Expression Inventory-2 (STAXI-2) and Beck Depression Inventory (BDI) item tools respectively. Result: The majority of our respondents were male (n=150/253, 59.3), had secondary level of education (104/253, 41.1) and were single (137/253, 54.2). No formal education and primary education (r2 = 47.4 and 6.4% respectively) had negative correlation with awareness of mental healthcare. In addition, no formal education had a positive correlation with anger and depression (r2 =1.9 and 0.3% respectively). Singleness in this study had a negative correlation with awareness of mental healthcare, anger, and depression (r2 =1.9, 0.8, and 0.3% respectively), and a positive correlation with anxiety (r2 =3.9%). Conclusion: It is evident that education and relationship status influenced awareness on mental healthcare and mental health state amongst low-income earners in Western Uganda during the first COVID-19 lockdown. Therefore, policymakers should strengthen social transformation, through the proper engagement of low-income earners in this COVID-19 era.